Addressing the Gap between Language Literacy and Physical Education: A Bilingual Socratic Play-Based Inquiry Model for Vocabulary and Grammar Development - Utami, Hadi Riwayati; Sumardiyani, Listyaning; Zahraini, Dian Ayu; Ambarini, Ririn (Amirul Bangun Bangsa Publishing, 2025)
This study aims to address the persistent gap between language literacy and physical education by developing and implementing a Bilingual Socratic Play-Based Inquiry Model designed to enhance students’ vocabulary and grammar development. Employing a qualitative descriptive design, the research involved a purposive sample of elementary students participating in integrated English–Physical Education learning sessions. Data were collected through classroom observations, learning artefacts, field notes, and semi-structured interviews with students and teachers. The key variables examined included bilingual interaction patterns, vocabulary acquisition, grammar awareness, and engagement through physical activities. Data were analyzed using thematic analysis to identify patterns of linguistic development emerging from play-based inquiry tasks. The findings revealed that combining Socratic questioning with kinesthetic, game-based activities fostered deeper vocabulary retention, improved grammar accuracy, and increased learner motivation. Students demonstrated stronger metalinguistic awareness when guided through dialogues that connected physical actions with target linguistic forms. The study concludes that a bilingual Socratic play-based inquiry approach is an effective instructional model for bridging disciplinary gaps, promoting meaningful language use, and supporting holistic literacy development within physical education contexts. Future research may explore the model’s long-term impact, scalability across grade levels, and adaptability for multilingual or inclusive classroom.